RESPONSE SURFACE METHODOLOGY AND DESIRABILITY FUNCTION AS STATISTICAL TOOLS IN THE OPTIMIZATION OF ELECTROCOAGULATION PROCESS IN SURFACE WATER - Efraim Lázaro Reis; Maria Paulina Mendonza Combatt; Karina Esther Vasquez Sanjuan; Antônio Augusto Neves; Regina Célia Santos Mendonça (The Journal of Engineering and Exact Sciences)
The electrocoagulation for water clarification for purification have been studied as alternative to the processes of the water treatment. This study aimed to model and to optimize this process for types of water with different turbidity conditions; considering the current intensity, electrolysis time and initial pH on apparent color removal, chemical oxygen demand and surface water turbidity. Electrocoagulation tests were make aluminum electrodes. The optimal operating conditions and models based on the response surface methodology were obtained with central composite design. In order to comply with the esthetic / organoleptic standard stipulated for this stage of the process, the characterization of the three types of water studied must have color < 15 uH, COD < 18 mg L-1 O2 and turbidity < 5 NTU). The correlation between the analyzed answers allows finding specific conditions of the parameters, assisting in the determination of safe work points in the operation of clarification.